p=7, q = 12.\\x_1+x_2 = -p => x_1+x_2 = -7\\x_1x_2 = q => x_1x_2 = 12.\\x^2 + 7x + 12 = 0\\x^2 + 2*\frac{7}{2}x + \frac{49}{4} - \frac{49}{4} + 12 = 0\\ (x+\frac{7}{2})^2 = \frac{1}{4}\\ (x+\frac{7}{2})^2 - (\frac{1}{2})^2 = 0\\ (x+\frac{7}{2}+\frac{1}{2})(x+\frac{7}{2}-\frac{1}{2})=0\\(x+4)(x+3)=0\\x_1 = -4\\x_2=-3\\" alt="x^2 + px + q = 0\\x^2 + 7x + 12 = 0 => p=7, q = 12.\\x_1+x_2 = -p => x_1+x_2 = -7\\x_1x_2 = q => x_1x_2 = 12.\\x^2 + 7x + 12 = 0\\x^2 + 2*\frac{7}{2}x + \frac{49}{4} - \frac{49}{4} + 12 = 0\\ (x+\frac{7}{2})^2 = \frac{1}{4}\\ (x+\frac{7}{2})^2 - (\frac{1}{2})^2 = 0\\ (x+\frac{7}{2}+\frac{1}{2})(x+\frac{7}{2}-\frac{1}{2})=0\\(x+4)(x+3)=0\\x_1 = -4\\x_2=-3\\" align="absmiddle" class="latex-formula">